Formalizing human ignorance collision-resistant hashing without the keys - Phillip Rogaway (2018)
There is a rarely mentioned foundational problem involving collision-resistant hash-functions: common constructions are keyless, but formal definitions are keyed. The discrepancy stems from the fact that a function H: {0,1}*→ {0, 1}nalways admits an efficient collision-finding algorithm, it's just that us human beings might be unable to write the program down. We explain a simple way to sidestep this difficulty that avoids having to key our hash functions. The idea is to state theorems in a way that prescribes an explicitly-given reduction, normally a black-box one. We illustrate this approach using well-known examples involving digital signatures, pseudorandom functions, and the Merkle-Damgård construction. © Springer-Verlag Berlin Heidelberg 2006.